The role of project-based learning in engineering curriculum: the case of the industrial engineering and management program at the University of Minho - Mesquita, Diana (2015)
One of the key questions arising from literature in Higher Education is the mismatch between curriculum and professional practice. This work presents an analysis of an engineering program, based on a model of curriculum development that includes three dimensions: professional profile, curriculum elements and framework of competences. These dimensions were considered in the methodological approach that involves a case study of the Industrial Engineering and Management (IEM) program at the University of Minho, Portugal. Data were collected through a combination of methods, including a survey, narratives, interviews and focus group. The aim was to get to know the perceptions of students and teachers of IEM program and professionals working in this engineering field. The findings highlight the relevance of projectbased learning within the engineering curriculum in so far as it provides students with opportunities to develop both technical and transversal competences related to their professional practice. This implies developing learning situations in which it is possible to solve engineering problems, linking theory and practice based upon an interdisciplinary approach. Furthermore, the implementation of project-based learning have implications for curriculum development, namely in regard to the definition of the assessment (e.g. milestones, feedback, etc.), coordination and communication between the faculty, content selection according to the problem to be solved, amongst other issues with impact in teaching practice.